Antiproliferative activity of pristimerin isolated from Maytenus ilicifolia (Celastraceae) in human HL-60 cells - da Costa, Patricia Marcal; Pinheiro Ferreira, Paulo Michel; Bolzani, Vanderlan da Silva [UNESP]; Furlan, Maysa [UNESP]; Formenton Macedo dos Santos, Vania Aparecida de Freitas [UNESP]; Corsino, Joaquim; de Moraes, Manoel Odorico; Costa-Lotufo, Leticia Veras; Montenegro, Raquel Carvalho; Pessoa, Claudia (Pergamon-Elsevier B.V. Ltd, 2008)
Pristimerin has been shown to be cytotoxic to several cancer cell lines. In the present work, the cytotoxicity of pristimerin was evaluated in human tumor cell lines and in human peripheral blood mononuclear cells (PBMC). This work also examined the effects of pristimerin (0.4; 0.8 and 1.7 mu M) in HL-60 cells, after 6, 12 and 24 h of exposure. Pristimerin reduced the number of viable cells and increased number of non-viable cells in a concentration-dependent manner by tripan blue test showing morphological changes consistent with apoptosis. Nevertheless, pristimerin was not selective to cancer cells, since it inhibited PBMC proliferation with an IC50 of 0.88 PM. DNA synthesis inhibition assessed by 5-bromo-2'-deoxyuridine (BrdU) incorporation in HL-60 cells was 70% and 83% for the concentrations of 0.4 and 0.8 mu M, respectively. Pristimerin (10 and 20 mu M) was not able to inhibit topoisomerase 1. In AO/EB (acridine orange/ethidium bromide) staining, all tested concentrations reduced the number of HL-60 viable cells, with the occurrence of necrosis and apoptosis in a concentration-dependent manner, results in agreement with trypan blue exclusion findings. The analysis of membrane integrity and internucleosomal DNA fragmentation by flow cytometry in the presence of pristimerin indicated that treated cells underwent apoptosis. The present data point to the importance of pristimerin as representative of an emerging class of potential anticancer chemicals, exhibiting an antiproliferative effect by inhibiting DNA synthesis and triggering apoptosis. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: pristimerin; apoptosis; antileukemic